2015
DOI: 10.1111/cen.12960
|View full text |Cite
|
Sign up to set email alerts
|

Phaeochromocytoma and ACTH‐dependent cushing's syndrome: tumour crf secretion can mimic pituitary cushing's disease

Abstract: Ectopic CRF production is biochemically indistinguishable from ectopic ACTH secretion, except that IPSS mimics pituitary Cushing's disease and cortisol dynamics may normalize rapidly postadrenalectomy. CRF secretion can be inferred through tumour immunohistochemistry, even if no CRF assay is available. Unrecognized phaeochromocytoma ACTH secretion may underpin some cases of cardiovascular collapse postadrenalectomy through acute hypocortisolaemia. Despite advances in phaeochromocytoma genetics since previous r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…Post-operative recovery from the clinical symptoms and elevated cortisol levels is much faster in patients with ectopic CRH syndrome than in those with ectopic ACTH syndrome [5, 8]. In the present case, the rapid postoperative recovery of clinical features, elevated serum ACTH, potassium and glucose levels, and short-term application of prednisone supported the classification of the pheochromocytoma as a CRH-secreting tumor, with ACTH secreted from the pituitary gland.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…Post-operative recovery from the clinical symptoms and elevated cortisol levels is much faster in patients with ectopic CRH syndrome than in those with ectopic ACTH syndrome [5, 8]. In the present case, the rapid postoperative recovery of clinical features, elevated serum ACTH, potassium and glucose levels, and short-term application of prednisone supported the classification of the pheochromocytoma as a CRH-secreting tumor, with ACTH secreted from the pituitary gland.…”
Section: Discussionsupporting
confidence: 61%
“…Quinton et al reported three patients with ACTH-dependent Cushing’s syndrome; in two cases, immunostaining showed reactivity for CRH instead of ACTH, supporting CRH (or related peptide) -secreting pheochromocytoma [8]. In the current case, the patient’s rapidly deteriorating condition did not allow us to perform IPSS and adrenal vein sampling.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Furthermore, they have been shown to affect the results of dynamic tests and may generate false positive results during BIPSS (5, 6, 8, 10, 12, 17, 24, 25, 26, 27). CRH secretion induces diffuse hyperplasia of pituitary corticotroph cells which then oversecrete ACTH but may remain responsive to both exogenous dexamethasone and CRH.…”
Section: Discussionmentioning
confidence: 99%